Evaluasi Dosis CT Scan Kepala Trauma Terhadap Nilai I-DRL - Nur Ma'rifah, Alifatus Wahyu (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2026)
This study aims to analyze the correlation between age and Body Mass Index (BMI) with the Computed Tomography Dose Index Volume (CTDIvol) and Dose Length Product (DLP) in non-contrast head CT scans performed on trauma patients. This observational analytic study employed a retrospective approach involving 30 adult patient samples. The results showed an average CTDIvol value of 65.18 mGy, exceeding the national Diagnostic Reference Level (DRL) established by BAPETEN (60 mGy). Nevertheless, this value is consistent with the use of the standardized “Brain Trauma” protocol and a uniform tube voltage of 120 kV. The CTDIvol ranged from 42.4 mGy to 103 mGy, indicating data homogeneity, with an average DLP of 1779.97 mGy·cm, significantly surpassing the national DRL (1275 mGy·cm). The elevated DLP value is attributed to the scan length extending from the vertex to the cervical vertebra 7, in accordance with hospital standard operating procedures for ead trauma management. Multiple logistic regression analysis revealed that age and BMI did not have a significant effect on CTDIvol (age Sig.=0.986; BMI Sig.=0.000) nor on DLP (age Sig.=0.134; BMI Sig.=0.055). This indicates that the radiation dose is more influenced by consistent technical protocols than by patient characteristics.